(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article provides a refined author’s definition (definition) of the country’s mobilization economy as a category that characterizes its ability to produce the maximum amount of products, works, services in natural units of measurement in certain sectors to counter existing or potential threats to the existence of the state itself through the use of concentrated in state institutions the power of all available resources. The signs of mobilization and socialist economy in Russia are considered.